Meningkatkan Kemampuan Teknik Smash dalam Permainan Badminton pada Anak Tunarungu Melalui Metode Guided Discovery - Alya, Nabila Fitri; Ardisal, Ardisal (Jurnal Penelitian Pendidikan Khusus, 2023)
This research based on two students who did not understand the smash technique in badminton. Based on the results of the observations that have been made, it appears that the student has an interest and talent in badminton. The aim of this research is to improve smash technique skills using the guided discovery method for deaf children. Method research that choosen by, was classroom research consisting of two cycles. In each cycles there are 4 face-to-face sessions, conducted in several phases: planning, action implementation, observation and reflection. The data collection techniques used were: observation, recording and testing. Data analysis was performed using both quantitative and qualitative methods.The results of the research showed that the process of learning smash techniques in badminton for deaf children in class VIII was carried out using the increased guided discovery method. After being given action, R got a percentage of 86.11%, before being given action 19.44% and N got a percentage of 72.22% before being given action 16.67%. So it can be concluded that the research objectives in this study were achieved, with the conclusion that the guided discovery method can improve the ability of smash techniques in badminton games in deaf children.